Perencanaan Perawatan Mesin Pengupas Kulit Pinang - Ihsan Putra Erizal; Yuli Yetri; Nusyirwan Nusyirwan (Politeknik Negeri Padang, 2018)
Planner engine maintenance is an important thing to streamline the production process. Care planning for areca nut peeler has been carried out which includes the engine frame, electric motor, pulleys, V-belts, reservoirs, and spindle shaft. These components are expected to work optimally so that satisfying results are obtained. The care of the areca peeling machine consists of preventive treatments, repair treatments, total treatments. Preventive care consists of cleaning, lubrication and periodic checks. Repair treatments include blade maintenance, bearing maintenance, pulley care and belt. While total maintenance is carried out after the engine has been operating long enough. The results of treatment planning are made in the form of a treatment table. While the results of the maintenance process that has been done by the machine can operate properly and can produce maximally.